Polyurethanes based on thermoreversible networks designed by Diels-Alder reaction - O. Ursache; C. Gaina; V. Gaina (eXPRESS Polymer Letters, 2017)
Urethane bismaleimides (BMIs) were used in order to obtain crosslinked structures by their reaction with an aromatic trifuran compound. The Diels-Alder (DA) reaction between the maleimide and furan moieties was investigated using proton nuclear magnetic resonance (1H-NMR) spectroscopy for a model compound (CTF), due to the fact that the networks are insoluble in usual NMR solvents. The structure of the networks was confirmed by infrared spectroscopy. Thermal properties were investigated (by means of differential scanning calorimetry (DSC) and thermogravimetrical analyses (TGA)) and compared with the ones of similar compounds, previously obtained from the same BMIs and a different trifuran compound (which contains tertiary nitrogen in its structure). Mechanical and rheological properties were also investigated. The influence of the nature of the polyol from the BMIs structure and/or the influence of using a trifurylic compound with or without tertiary nitrogen on the properties of the crosslinked networks were also discussed.